Self-confidence Levels of Individuals performing Clean Intermittent Catheterization and the Affecting Factors - Elif Ateş; Şengül Üzen Cura; Berke Aras (Nursing and Health Sciences Journal (NHSJ), 2022)
This study aimed to determine the self-confidence levels of individuals with spinal cord injury, who performed clean intermittent catheterization (CIC), and the factors affecting their self-confidence. Descriptive cross-sectional study. The study was conducted on 107 individuals with spinal cord injury. The mean age was 39.26±13.46 years. Data were collected via Google Survey between March and September 2021. The mean Self-confidence Scale for Clean Intermittent Self-Catheterization (SCSCISC) score was 4.14±0.81, indicating relatively high levels of self-confidence. However, the participants obtained moderate scores from the items “what to do when there is blood in the urine” and “what to do when there is no urine”, which were 3.02±1.5 and 3.01±1.5, respectively. The SCSCISC scores were significantly higher for the participants, who were male, had a job, did not use medication for bladder problems and were functionally semi-independent or independent. General level of self-confidence was high but the participants did not know what to do when there was blood in the urine or when there was no urine. Self-confidence levels were influenced by age, gender, working status, functional independence and medication use for bladder problems.